Identification of miRNA–mRNA–TFs Regulatory Network and Crucial Pathways Involved in Tetralogy of Fallot - You, Guoling; Zu, Bailing; Wang, Bo; Fu, Qihua; Li, Fen (Frontiers in Genetics, 2020)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease. However, its pathogenesis remains unknown. To explore key regulatory connections and crucial pathways underlying the TOF, gene or microRNA expression profile datasets of human TOF were obtained from the NCBI Gene Expression Omnibus (GEO) database. The differential expression mRNAs (DEmRNAs) and microRNAs (DEmiRs) between TOF and healthy groups were identified after data pre-processing, followed by Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Then, we further constructed protein-protein interaction (PPI) network and subnetwork of modules. Ultimately, to investigate the regulatory network underlying TOF, a global triple network including miRNAs, mRNAs and transcription factors (TFs) was constructed based on the integrated data. In the present study, a total of 529 DEmRNAs, including 115 downregulated and 414 upregulated DEmRNAs, and 7 significantly upregulated DemiRs, including miR-499, miR-23b, miR-222, miR-1275, miR-93, miR-155, and miR-187, were found between TOF and control groups. Furthermore, 22 hub genes ranked by top 5% genes with high connectivity and six TFs, including SRF, CNOT4, SIX6, SRRM3, NELFA, and ONECUT3, were identified and might play crucial roles in the molecular pathogenesis of TOF. Additionally, a miRNA‑mRNA-TFs coregulatory network was established and indicated ubiquitin mediated proteolysis, energy metabolism associated pathways, neurodevelopmental disorders associated pathways and ribosome might involve in the pathogenesis of TOF. The current research provides a comprehensive perspective of regulatory mechanism networks underlying TOF and also identifies potential molecule targets of genetic counseling and prenatal diagnosis for TOF.